The biogeochemical evolution of the Coorong during the mid- to late Holocene: An elemental, isotopic and biomarker perspective - McKirdy, D.; Thorpe, C.; Haynes, D.; Grice, Kliti; Krull, E.; Halverson, G.; Webster, L. (Elsevier Science, 2010)
Since the mid-1990s the Coorong, a 130-km-long coastal wetland of international importance in southeastern South Australia, has undergone serious decline due largely to prolonged drought and reduced inflows of surface and ground water from its hinterland. Tenuously connected to the ocean at its northern extremity, it is effectively separated into two lagoons by a narrow channel at its mid-point. The southern part is now permanently hypersaline. Here we report the results of an attempt to track the biogeochemical status of the estuary over the last 5000 years employing a consortium of elemental, isotopic and biomarker parameters. The sediment samples analysed came from two cores, each 6-7 m in length, retrieved from sites located halfway along the present-day northern and southern lagoons. The sediments at the southern locality are richer in total organic carbon and total nitrogen than those in the northern core reflecting higher net deposition of organic matter (OM) and nutrients in the southern lagoon. Comparison of the delta C-13(org) and delta N-15 profiles of the two cores reveals that the lower reaches of the Coorong have always been a restricted, O-2 depleted water body that is both more saline and prone to more intensive denitrification of NO3- (aq) than the northern lagoon. Prominent among the aliphatic hydrocarbons preserved in the sediments of the southern lagoon are the C-20 highly branched isoprenoid (HBI), 2,6,10-trimethyl-7-(3-methylbutyl)-dodecane, a putative marker of epiphytic diatoms, and C-15-C-35 n-alkanes with a marked odd/even predominance in the C-21, range. These and other biomarkers are consistent with OM derived from a mixed population of algae, cyanobacteria and other eubacteria.The C isotopic signature of the HBI alkane is consistently heavier than those of the C-23, C-25, C-27 and C-29 n-alkanes (presumably from planktonic chlorophytes +/- aquatic metaphytes), which in turn are heavier than the coexisting even-carbon-numbered homologues of likely bacterial origin. With decreasing age these biomarker alkanes display an overall increased depletion in C-13 and enrichment in D, trends that have accelerated over recent decades as the south lagoon has become progressively more hypersaline and ecologically impoverished. However, coeval negative excursions in the delta D profiles of the epiphyte marker and n-alkanes, along with coincident diatom inferred reductions in palaeosalinity, together highlight a series of hitherto unrecognised freshening events attributable to enhanced inflow of surface runoff and shallow groundwater. C-13 NMR spectra confirm that this OM is largely algal derived, but with a significant contribution from the seagrass Ruppia megacarpa (and possibly other aquatic macrophytes), particularly in pre-European sediments.